Dietary Valine/Isoleucine Ratio Impact Carcass Characteristics, Meat Edible Quality and Nutritional Values in Finishing Crossbred Duroc × Landrace × Yorkshire Pigs With Different Slaughter Weights - Xu, Doudou; Wang, Yubo; Zhang, Xin; Yan, Enfa; He, Linjuan; Wang, Lu; Ma, Chenghong; Zhang, Pengguang; Yin, Jingdong (Frontiers in Nutrition, 2022)
The aim of this study was to investigate effects of dietary ratio of valine to isoleucine (R(V/I)) on carcass characteristics and meat quality of finishing pigs and whether slaughter weight influence the effect. We carried out a 2 × 3 factorial trial with two slaughter weight (105 vs. 130 kg) and three R(V/I) (0.58, 1.23 and 2.60 at 75-100 kg body weight , and 0.70, 1.24 and 2.39 at 100-135 kg body weight for L-, N- and H-R (V/I), respectively). Data show that increasing slaughter weight significantly increased meat color (a*45 min and b*45 min), drip loss and shear force (P < 0.05). Meanwhile, increasing slaughter weight reduced sarcomere length, the proportion of protein-bound water, and most kinds of muscular total amino acid contents except for tryptophan and arginine, while increased contents of muscular free lysine, tryptophan, leucine, isoleucine, valine, alanine, and arginine in the M. longissimus thoracis (P < 0.05). Health lipid indices based on fatty acid composition of intramuscular lipid were improved as the slaughter weight increased (P < 0.05). Notably, pigs received N-R (V/I) diet improved carcass traits in terms of thinner backfat thickness and higher fat-free lean index, as well as increased meat flavor-contributing amino acids at the cost of reduced intramuscular fat content and increased shear force of cooked meat compared with the pigs fed L-R (V/I) and H-R(V/I) diets (P < 0.05). H-R (V/I) diet decreased ultimate pH value and sarcomere length of the skeletal muscle but increased the proportion of free water (T23), consequently, increased drip loss and cooking loss of fresh meat in pigs (P < 0.05). In conclusion, both slaughter weight and dietary ratio of valine to isoleucine exerted significant impacts on carcass characteristics, meat quality and nutrition values. In particular, carcass traits and meat color of lighter pigs were more susceptible to the influence of dietary R (V/I) relative to heavier pigs.